Avoiding Drug Carryover During Feed Processing and Delivery - Harner III, Joseph P.; Herrman, Tim J.; Falk, John; Behnke, Keith (My University, 1996)
This publication provides information for feed manufacturers that will help them avoid drug carryover.
MF2055_1996_03
Keywords: MF2055; Equipment and structures; Crops; livestock; MF